2014
DOI: 10.1111/nmo.12388
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of sacral nerve stimulation mechanisms in the treatment of fecal incontinence and constipation

Abstract: The initial hypothesis that the mechanism of SNS was primarily peripheral motor neurostimulation is not supported by the majority of recent studies. Due to the large body of evidence demonstrating effects outside of the anorectum, it appears likely that the influence of SNS on anorectal function occurs at a pelvic afferent or central level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
126
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 105 publications
3
126
1
4
Order By: Relevance
“…Thirteen published studies were found reporting the use of SNS for constipation. 201 Ten studies involved adult subjects, including two double-blind crossover studies and three were retrospective reviews. SNS appears to be an effective treatment for constipation; however, research to date has been predominantly confined to small, low-level evidence studies with most lacking a coherent definition of constipation and SNS.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 99%
“…Thirteen published studies were found reporting the use of SNS for constipation. 201 Ten studies involved adult subjects, including two double-blind crossover studies and three were retrospective reviews. SNS appears to be an effective treatment for constipation; however, research to date has been predominantly confined to small, low-level evidence studies with most lacking a coherent definition of constipation and SNS.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 99%
“…In a recent systematic study, 53 of 161 clinical studies that investigated cortical, gastrointestinal, rectal, and anal functions and 9 of 43 experimental studies were evaluated. Although sufficient information in this systematic study regarding the mechanism was lacking, it was concluded that the mechanism of action of sacral stimulation on anal dysfunction and constipation may be via pelvic afferents or a central effect, rather than primarily via peripheral motor neurostimulation (46). A significant proportion of findings demonstrate that irritable bowel syndrome and other functional bowel diseases can be treated with sacral stimulation (43).…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%
“…According to expert opinion, an improvement of less than 50 % shall result in an extended testing period. An improvement of symptoms of at least 30 % combined with an improved quality of life may be considered an indication for implantation [26,27].…”
Section: Item 48mentioning
confidence: 99%